PENGARUH FINANCIAL DISTRESS DAN LEVERAGE TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR SUBSEKTOR FOOD AND BAVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Apriliana, Linda; Nisa, Lita Khoirun; Prastika, Rikke (STIE Perbankan Indonesia, 2024)
This study aims to examine the influence of financial distress and leverage on earnings management in food and beverage manufacturing companies listed on the Indonesia Stock Exchange for the period 2019-2023. Using a quantitative approach, this research analyzed a sample of 10 companies selected through purposive sampling. The research employed multiple linear regression analysis to test the hypotheses. The results show that financial distress has a significant negative effect on earnings management, contrary to the initial hypothesis. Leverage, however, does not show a significant influence on earnings management. When analyzed together, financial distress and leverage demonstrate a significant impact on earnings management, with the research model explaining 64.3% of the variation in earnings management practices. These findings provide new insights for investors, regulators, and other stakeholders in assessing the quality of company financial reports and open opportunities for further research on financial reporting dynamics under various financial conditions of companies in Indonesia. Keywords: Earnings Management, Financial Distress, Leverage